Mechanism of Mo-Dependent Nitrogenase - Seefeldt, Lance C. (2009)
Nitrogen-fixing bacteria catalyze the reduction of dinitrogen (N(2)) to two ammonia molecules (NH(3)), the major contribution of fixed nitrogen into the biogeochemical nitrogen cycle. The most widely studied nitrogenase is the Mo-dependent enzyme. The reduction of N(2) by this enzyme involves the transient interaction of two component proteins, designated the Fe protein and the MoFe protein, and minimally requires sixteen MgATP, eight protons, and eight electrons. The current state of knowledge on how these proteins and small molecules together effect the reduction of N(2) to ammonia is reviewed. Included is a summary of the roles of the Fe protein and MgATP hydrolysis, information on the roles of the two metal clusters contained in the MoFe protein in catalysis, insights gained from recent success in trapping substrates and inhibitors at the active site metal cluster FeMo-cofactor, and finally, considerations of the mechanism of N(2) reduction catalyzed by nitrogenase.